Significance of Reticulocyte Count in Assessment of Pancytopenia at Tertiary Care Hospital - Maria Shaikh, Humera Shaikh, Raima Kalhoro, Safiya Javed, Anita George, Kiran Memon, Kiran Aamir, Aamir Ramzan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the significance of reticulocyte count in assessment of pancytopenia. Study Design: Retrospective study Place and Duration: Department of Pathology, Diagnostic and research Laboratory LUMHS, Hyderabad. Jan 2017-Oct 2018. Methods: The study comprised a total of one hundred pancytopneia patients. The comprehensive demographics of the enrolled cases were collected upon obtaining informed written consent. The diagnostic utility of absolute reticulocyte count was determined by correlating it with bone marrow biopsy. SPSS 22.0 was used to analyze the data. Results: Among all, 43% were males and 57% were females. Age of the presented cases was 35.3±2.54 years. 62% patients were married and 37% cases were literate. Majority 59% patients were from rural areas. Megaloblastic anemia was the most common etiology found in 52% cases with reticulocyte count 0.2%, aplastic anemia in 22% cases with reticulocyte count 0.1%, mixed deficiency anemia in 17% reticulocyte count 0.4%, acute leukemia in 6% with reticulocyte count 0.7% and 3% cases had myelodysplastic syndrome with reticulocyte count 0.2%. The most frequent clinical features that were present were pallor (88%), generalized weakness (81%), dyspnea (62%), and fever (60%). Conclusion: Reticulocyte count plays an important role in differentiating various causes of pancytopenia and hence should be routinely included in pancytopenia work up in order to avoid unnecessary bone marrow aspirations. Keywords: Pancytopneia, Reticulocyte count, Fever, Pallor, Biopsy